Lipid profile in ?-thalassemia major children and its correlation with various parameters - Priya Daswani,; Kapil Garg, (Indian Journal of Child Health, 2021)
Background: Beta-thalassemia is considered to be the most frequent hereditary blood disorder worldwide. Lipid abnormalities have been detected in different types of beta-thalassemia thus pre-disposing them to pre-mature atherosclerosis. Objectives: To study the lipid profile in beta-thalassemia major (?-TM) children and establish its co-relation with various parameters. Materials and Methods: A total of 100 diagnosed patients of ?-TM age 1–18 years and 100 subjects in the control group matched for age and sex were enrolled. For detecting a minimum difference of at least 20 mg/dl of triglyceride between the two groups, the required sample size was 81 subjects in each group, which was further, enhanced and rounded off to 100 subjects in each group. Univariate and multivariate regression analysis was done to establish a correlation of lipid profile with various parameters. Results: Total cholesterol (TC) was lower in thalassemia patients as compared to controls 104.45 versus 117.97 (p